IL6ST: A Novel Therapeutic Target for Managing and Treating Colorectal Cancer Via Ferroptosis - Zhao, Kun; He, Baoguo; Xue, Kuijin; Cao, Bin; Ren, Keyu; Jin, Yanchun; Rong, Shanwei; Wei, Liangzhou; Wei, Hongyun (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Inflammation is an essential driver of colorectal cancer (CRC). Identifying phenotypes and targets associated with inflammation and cancer may be an effective way to treat CRC. Materials and Methods: R was used to analyze interleukin 6 cytokine family signal transducer (IL6ST) expression in The Cancer Genome Atlas Colon Adenocarcinoma database. Immunohistochemistry, western blotting, and quantitative PCR were used to detect IL6ST and ferroptosis-related genes expression in our cohort. Receiver operating characteristic curves evaluated the specificity and sensitivity of IL6ST to predict CRC. Cell counting kit-8 investigated cell viability. Mitochondrial morphology, total iron, and reactive oxygen species (ROS) levels were evaluated to assess cell ferroptosis. The correlation of IL6ST and immune cells filtration were also analyzed based on R. Results: IL6ST was significantly upregulated in CRC tissues (P < .05). The specificity and sensitivity of IL6ST for predicting CRC were high (area under the curve (AUC): 0.919, CI: 0.896-0.942). IL6ST was significantly associated with ferroptosis-related genes. IL6ST knockdown decreased SW480 cells viability (knockdown vs. vector, P = .004), promoted the ferroptosis phenotype, and increased iron accumulation (knockdown vs. vector P = .014) and ROS production (knockdown vs. vector P = .005). IL6ST upregulation increased SW620 cells viability (overexpression vs. blank, P = .001), inhibited the ferroptosis phenotype, and decreased iron accumulation (overexpression vs. vector P = 0.006) and ROS production (overexpression vs. vector P = .05). IL6ST increased FTH1 and GPX4 expression and reduced PTGS2, NOX1, and ACSL4 expression (P < .01). Additionally, IL6ST level is linked to immune cell infiltration. A higher enrichment score of T cells was observed in IL6ST up-regulated group. Conclusion: IL6ST inhibits ferroptosis and may be a potential novel therapeutic target in CRC via the modulation of ferroptosis. Cite this article as: Zhao K, He B, Xue K, et al. IL6ST: A novel therapeutic target for managing and treating colorectal cancer via ferroptosis. Turk J Gastroenterol. 2024;35(9):690-698.